Wet and Dry Spell Analysis for Crop Planning in Central Plain Zone of Punjab Using Markov Chain Method - Chand, Shivani; Dhaliwal, L. K. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted during 2017–2018 at department of climate change and agricultural meteorology, PAU, Ludhiana to find out the initial and conditional probability of occurrence of wet and dry spell of rainfall at different locations of Punjab, the analysis was carried out using Markov Chain Method (MCM). The historical data of rainfall for three locations of Punjab viz. Amritsar (1971–2017), Ludhiana (1971–2018) and Patiala (1971–2018) were collected from the Department of Climate Change and Agricultural Meteorology, PAU, Ludhiana and Met Centre, India Meteorological Department, Chandigarh. At Amritsar the chances of occurrence of wet spell were highest during 28th SMW i.e., 72% followed by 68% during 30th and 31st SMW respectively. The conditional probability calculated at Ludhiana showed that the probability of wet spell followed by wet spell was highest (71%) during 28th SMW followed by 66 per cent during 30th and 32nd SMW. At Patiala the probability of wet spell was highest (69%) during 33rd week followed by 63% during 29th SMW. The conditional probability also showed that dry spell followed by dry spell occurred more frequently than wet spell followed by wet spell.